Contributions of hemispheric dynamics in visual word recognition: uncovering familiarity effects through lateralized priming - Kim, Sangyub; Nam, Kichun (Frontiers in Psychology, 2024)
The present investigation aimed to explore interhemispheric interactions in the visual word processing, particularly focusing on proficiency development. Employing a primed-lateralized lexical decision task with a stimulus onset asynchrony (SOA) of 100 ms, we assessed behavioral responses based on parafoveal visual fields (left visual field/right visual field) of prime and target stimuli. Leveraging the familiarity effect as a gauge of visual word processing proficiency, our hypothesis posited that the primary hemisphere predominantly regulates interhemispheric interactions due to the asymmetrical specialization observed in visual word processing across hemispheres.Our findings revealed a significant interhemispheric familiarity effect in response times when the left visual field (LVF)/right hemisphere (RH) served as the prime and the right visual field (RVF)/left hemisphere (LH) as the target. Furthermore, we identified a significant intrahemispheric familiarity effect in response times within the LVF/RH condition, highlighting the significance of RH visual-perceptual processing in the developmental trajectory of proficiency in visual word recognition concerning interand intrahemispheric interactions. These outcomes furnish compelling evidence of asymmetric specialization between hemispheres and offer valuable insights into interhemispheric dynamics during the evolution of visual word recognition proficiency.